ASSESSMENT OF CADMIUM CONTAMINATION AND ACCUMULATION IN MAIZE (ZEA MAYS L.) AND AGRICULTURAL SOILS - Abderrazzak, Baba Ahmed; Keltoum, Bouhadjera (European Scientific Journal, ESJ, 2014)
Accumulation of heavy metals in soils from different sources (atmospheric deposition, industrial activities and urban, agricultural practices ...) should be studied and followed because of persistent and potentially toxic to these chemical compounds. Determining the bioavailability of heavy metals the chemical form in which they find themselves is a necessary step to determine the ecotoxicological risks for organisms in contaminated soil. Soil pollution by cadmium (Cd), a metal which is potentially toxic to humans because of its high mobility in soil, bioavailability through the food chain, and its impact on kidney in case of chronic exposure through the diet. In this study an assessment is done concerning the impact of soils on heavy metals contamination of maize. In this work, we have studied the distribution and migration of cadmium in different soil horizons it was applied on a site widely cultivated with maize in Algeria. The soil was subjected to chemical characterisation, total metal quantification (Cd) sequential extraction as well metal speciation in 2011. Cadmium concentrations exceeded the acceptable limits in soils, with strong surface accumulations and a rapid decrease of the pollution with depth. However, in the edible portion of maize, the cadmium concentrations were higher than the permitted limits of the european standard. As for the plants grown, the study indicates a potential ecological risk of maize contamination by cadmium.